Legal Protection of Cultural Objects in the Armed Conﬂict - Akbar Kurnia Putra; Bernard Sipahutar; Vrandza Iswenanda; Sulhi Muhammad Daud (Faculty of Law, Jambi University, 2019)
This article aims to overview how the International Humanitarian Law regulates the protection of cultural heritages at the event of armed conﬂict. Applying a normative legal method, this article coclude that the protection for the cultural objects during an armed conﬂict is regulated in the Hague Convention IV of 1907, the Geneva Conventions IV of 1949, the Hague Convention of 1954, and the Second Protocols to the Hague Convention of 1954 for the Protection of Cultural Property in the Event of Armed Conﬂict 1999. The Hague Convention of 1954 mentions about safeguarding of the cultural property from any harm as a result of armed conﬂicts and about respect for the cultural objects. Each nation is responsible to avoid, prevent, and forbid any harfmul acts against cultural property. However, no stipulation is mentioned on how the victims whose cultural objects are destroyed could sue for any destructions. Therefore it is recommended that a special International Body be formed to supervise any harmful activities toward the cultural objects. Such a body might be more than just an International Court of Justice whose function is to settle any objections, sues, or claims from parties whose cultural objecs have been destroyed during armed conﬂicts.